Determinant of Nurse Performance in the Era of the COVID-19 Pandemic in Bali - Oyagi Ryusuke; Luh Putu Mahyuni (Faculty of Economics and Business Udayana University, 2021)
During the COVID-19 pandemic, medical personnel received much heavier workload than normal. On top of it, stigma and low appreciation of the community for medical personnel leads to increase of both physical and psychological pressure. The purpose of this study is to analyze the effect of leadership, workload, and work environment on nurse satisfaction and performance. The sample in this study were 246 nurses who worked at Bali Mandara Hospital. Data was collected through questionnaire distributed online using google form platform and the data was processed using SmartPLS 3.2.1. The results of the study found that: (1) leadership, workload, and work environment had a positive and significant effect on nurses' job satisfaction; (2) leadership and nurse satisfaction have a positive and significant effect on nurse performance, workload has a negative and significant effect on nurse performance, and work environment has no effect on nurse performance; and (3) nurse job satisfaction mediates the influence of leadership, work load, and work environment on nurse performance.